Pengaruh Kesadaran Dan Pendapatan Terhadap Kepatuhan Membayar Zakat - Azmila Sakinah Br Purba, Yaumul Khair Afif, Khairunnisa (Pusdikra Publishing, 2022)
The aim of this study was to determine the partial or simultaneous effect of awareness and income on the compliance of the people of the Besitang District in paying zakat. The data source for this research was obtained from questionnaire answers given by research respondents, namely muzakki in Besitang District with a total of 98 respondents. Data analysis in this study used validity test, reliability test, classical assumption test, hypothesis test, and multiple linear regression analysis. Based on this test it is explained that there is a significant influence of awareness on the compliance of the people of Besitang Subdistrict paying zakat, this is obtained from the hypothesis test, namely the t test which shows the variable Awareness (X1) statistically shows a significance value of less than 0.05 or (0.003 < 0.05) and tcount > ttable (3.018 > 1.98525) so that there is an effect of variable X on variable Y. There is a significant effect of income on the compliance of the people of Besitang District in paying zakat, this is obtained from the hypothesis test, namely the t test which shows the variables Income (X2) statistically shows a significance value of less than 0.05 or (0.000 <0.05) and tcount > ttable (4.603 > 1.98525) so there is an effect of variable X on variable Y. Simultaneously or together there is significant influence between awareness and income on compliance to pay zakat society of Besitang District, ha l This was obtained from the hypothesis test, namely the f test obtained an Fcount of 30.906 with a significance value of 0.000. Because the significance value is less than 0.05 (0.000 <0.05) and the value of Fcount > Ftable (30.906 > 3.09), the independent variables simultaneously affect the dependent variable.